Age moderates the association of depressive symptoms and unhealthy alcohol use in the National Guard. (December 2016) - Sahker, Ethan; Acion, Laura; Arndt, Stephan
Abstract: Unhealthy drinking is a significant problem contributing to poor health and performance of military personnel. The Iowa Army National Guard and the Iowa Department of Public Health have collaborated with the Substance Abuse and Mental Health Administration to better identify unhealthy substance use via Screening, Brief Intervention, and Referral to Treatment program (SBIRT). Yet, little research has been conducted on the Guard's use of SBIRT. This study examined depression, age, deployment status, and sex as factors contributing to unhealthy drinking. Of the Guardsmen who took part in SBIRT, 3.7% (n = 75) met the criteria for unhealthy drinking and 3.9% (n = 78) had some level of depression. The overall multivariate model significantly predicted unhealthy drinking (χ 2 (5) = 41.41, p < 0.001) with age moderating the association of depressive symptoms and unhealthy alcohol (Wald χ 2 (1) = 7.16, p = 0.007). These findings add to the existing understanding of factors contributing to unhealthy drinking suggesting the association between the presence of depression and unhealthy drinking depends on age of the Guradsman. This age and depression interaction may be an important diagnostic feature to consider for unhealthy drinking in the Guard. Furthermore, previous research on the general military population finds similar percentages, providing support for SBIRT as an effective screening tool in the Guard. Highlights: Depression, sex, and deployment did not predict Guardsmen's unhealthy drinking. Guardsmen's depressive symptoms and unhealthy drinking depend on age. Depression is related to unhealthy drinking only for Guardsmen over 33 years old. SBIRT with Guardsmen appears effective in identifying unhealthy drinking.